2010
DOI: 10.1161/atvbaha.110.207076
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood–Derived Endothelial Cells Reendothelialize Vein Grafts and Prevent Thrombosis

Abstract: Objective-To accelerate vein graft reendothelialization and reduce vein graft thrombosis by infusing human umbilical cord blood-derived endothelial cells (hCB-ECs) because loss of endothelium contributes to vein graft thrombosis and neointimal hyperplasia. Methods and Results-Under steady flow conditions in vitro, hCB-ECs adhered to smooth muscle cells 2.5 to 13 times more than ECs derived from peripheral blood or human aorta (PϽ0.05). Compared with peripheral blood and human aorta ECs, hCB-ECs had 1.4-fold mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Based on the previous studies we conducted, we observed growth factors reduced the rate of EC growth, but did not arrest growth as observed in the coculture conditions of this study. 22,25 A decrease in EC proliferation during network formation is consistent with angiogenesis observed in vivo and may support a stable and quiescent state for capillary networks. 26 These results suggest that coculture is a suitable way to promote stable EC networks in vitro.…”
supporting
confidence: 72%
“…Based on the previous studies we conducted, we observed growth factors reduced the rate of EC growth, but did not arrest growth as observed in the coculture conditions of this study. 22,25 A decrease in EC proliferation during network formation is consistent with angiogenesis observed in vivo and may support a stable and quiescent state for capillary networks. 26 These results suggest that coculture is a suitable way to promote stable EC networks in vitro.…”
supporting
confidence: 72%
“…Consequent to the barotrauma associated with implantation in the arterial circuit, 3, 24, 28 defects in the vein graft endothelium trigger platelet adhesion to the vein graft’s luminal surface; platelet-secreted SDF-1 29 then functions to recruit vein graft-extrinsic cells to the vein graft. During vein graft arterialization, cells of the burgeoning vein graft media and neointima also secrete SDF-1—as Fig 2 demonstrates.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of endothelial and mural cell coculture, vascular smooth muscle cells (VSMCs) secrete basement membrane proteins that enable adhesion of endothelial cells (ECs). [1][2][3][4] In addition, proangiogenic factors released by VSMCs promote development and stabilization of capillaries. VSMCs and ECs grow in a three-dimensional (3D) multilayered structure similar to vascular wall structure.…”
mentioning
confidence: 99%